A novel alkylating agent Melflufen induces irreversible DNA damage and cytotoxicity in multiple myeloma cells. (20th April 2016) - Ray, Arghya; Ravillah, Durgadevi; Das, Deepika S.; Song, Yan; Nordström, Eva; Gullbo, Joachim; Richardson, Paul G.; Chauhan, Dharminder; Anderson, Kenneth C.
Summary: Our prior study utilized both in vitro and in vivo multiple myeloma (MM) xenograft models to show that a novel alkylator melphalan‐flufenamide (Melflufen) is a more potent anti‐MM agent than melphalan and overcomes conventional drug resistance. Here we examined whether this potent anti‐MM activity of melflufen versus melphalan is due to their differential effect on DNA damage and repair signalling pathways via γ‐H2AX/ATR/CHK1/Ku80. Melflufen‐induced apoptosis was associated with dose‐ and time‐dependent rapid phosphorylation of γ‐H2AX. Melflufen induces γ‐H2AX, ATR, and CHK1 as early as after 2 h exposure in both melphalan‐sensitive and –resistant cells. However, melphalan induces γ‐H2AX in melphalan‐sensitive cells at 6 h and 24 h; no γ‐H2AX induction was observed in melphalan‐resistant cells even after 24 h exposure. Similar kinetics was observed for ATR and CHK1 in meflufen‐ versus melphalan‐treated cells. DNA repair is linked to melphalan‐resistance; and importantly, we found that melphalan, but not melflufen, upregulates Ku80 that repairs DNA double‐strand breaks. Washout experiments showed that a brief (2 h) exposure of MM cells to melflufen is sufficient to initiate an irreversible DNA damage and cytotoxicity. Our data therefore suggest that melflufen triggers a rapid, robust, and an irreversible DNA damage which may account for its ability to overcome melphalan‐resistance in MM cells.